Data from: Early-life conditions determine the between-individual heterogeneity in plasticity of calving date in reindeer ... - Paoli, Amelie; Weladji, Robert B.; Holand, Øystein; Kumpula, Jouko (Dryad, 2020)
1. Phenotypic plasticity has become a key-concept to enhance our ability to understand the adaptive potential of species to track the pace of climate change by allowing a relatively rapid adjustment of life history traits. 2. Recently, population-level trends of an earlier timing of reproduction to climate change have been highlighted in many taxa but only few studies have explicitly taken into consideration between-individual heterogeneity in phenotypic plasticity. 3. Using a long-term data of a semi-domesticated reindeer (Rangifer tarandus) population, we demonstrated that females differed greatly in their mean calving date but only slightly in the magnitude of their plastic response to the amount of precipitation in April. We also showed that despite the absence of a population trend, females individually responded to the amount of precipitation in April by delaying their calving dates. 4. Females’ calving date under average climatic conditions was best predicted by their birthdate, their physical ... : Full dataAll the abbreviated variable names are described in detail in the paper. Variables not provided in abbreviation in the paper are not abbreviated here, but provided in full text.data.csv ...